2022
DOI: 10.3390/su141711084
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Factors Affecting a Career Shifter’s Use of Software Testing Tools amidst the COVID-19 Crisis in the Philippines: TTF-TAM Approach

Abstract: The restrictions of the ongoing COVID-19 pandemic resulted in the downturn of various industries and in contrast a massive growth of the information technology industry. Consequently, more Filipinos are considering career changes to earn a living. However, more people still need to be upskilled. This study combines the extended Technology Acceptance Model and Task Technology Fit framework to determine factors affecting a career shifter’s use of software testing tools and its impact on perceived performance imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…Although surprising and not aligned with most studies, the finding is in line with Sanni et al (2013) and Wu and Wu (2005). Furthermore, this result also aligns with several TAM and UTAUT studies where the perceived usefulness and performance expectancy have not always affected the intention to use (Ong et al, 2022;Sharif et al, 2019). One plausible reason could be the measurement timing.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Although surprising and not aligned with most studies, the finding is in line with Sanni et al (2013) and Wu and Wu (2005). Furthermore, this result also aligns with several TAM and UTAUT studies where the perceived usefulness and performance expectancy have not always affected the intention to use (Ong et al, 2022;Sharif et al, 2019). One plausible reason could be the measurement timing.…”
Section: Discussionsupporting
confidence: 67%
“…TTF has been integrated with the abovementioned theories, such as TAM and UTAUT. The findings have shown that TTF indirectly influenced the successful adoption and utilization of technologies via perceived ease of use, such as for wearable devices (Chang et al, 2016) and knowledge management systems (Kuo & Lee, 2011), as well as through perceived usefulness (Ong et al, 2022). On the other hand, TTF indirectly influenced the usage intention of smart home healthcare services positively via performance expectancy (Kang et al, 2022) and affected effort expectancy in a learning management system (Sharif et al, 2019).…”
Section: Task-technology Fit (Ttf)mentioning
confidence: 99%
“…This study has theoretically proved the soundness and robustness of the research framework built on the combination of TTF, TAM, and UTAUT designed to analyze the BI and PI of users. Furthermore, besides providing a robust model, this study provides a novel and testable methodology related to applying MASEM [73]. Consequently, this study theoretically contributes to the literature on MASEM methodology and proposes a new testable methodology for other scholars to use in various fields.…”
Section: -1-theoretical Implicationsmentioning
confidence: 92%
“…However, there are some limitations regarding capturing cultural and individual characteristics [80]. Hence, future researchers are advised to include TPB and system usability scales to study the cultural context [73].…”
Section: -3-research Limitations and Future Research Suggestionsmentioning
confidence: 99%
“…For example, Teo et al [ 34 ] found that teachers with high computer self-efficacy tend to perceive technology as easy to use. Similarly, a study on software testers identified computer self-efficacy as a robust predictor of perceived ease of use of software testing tools [ 35 ]. The correlation has also been found in the context of e-learning.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%